Ligand‐Based Control of Single‐Site vs. Multi‐Site Reactivity by a Trichromium Cluster. Issue 17 (27th March 2019) - Bartholomew, Amymarie K.; Juda, Cristin E.; Nessralla, Jonathon N.; Lin, Benjamin; Wang, SuYin Grass; Chen, Yu‐Sheng; Betley, Theodore A.
Abstract: The trichromium cluster ( tbs L)Cr3 (thf) ([ tbs L] 6− =[1, 3, 5‐C6 H9 (NC6 H4 ‐ o ‐NSi t BuMe2 )3 ] 6− ) exhibits steric‐ and solvation‐controlled reactivity with organic azides to form three distinct products: reaction of ( tbs L)Cr3 (thf) with benzyl azide forms a symmetrized bridging imido complex ( tbs L)Cr3 ( μ 3 ‐NBn); reaction with mesityl azide in benzene affords a terminally bound imido complex ( tbs L)Cr3 ( μ 1 ‐NMes); whereas the reaction with mesityl azide in THF leads to terminal N‐atom excision from the azide to yield the nitride complex ( tbs L)Cr3 ( μ 3 ‐N). The reactivity of this complex demonstrates the ability of the cluster‐templating ligand to produce a well‐defined polynuclear transition metal cluster that can access distinct single‐site and cooperative reactivity controlled by either substrate steric demands or reaction media. Abstract : All together now : A reactive trichromium complex synthesized using a templating ligand undergoes controllable, single‐site, and cooperative reactivity with organic azides. By varying the steric profile of the azide substrate, it is possible to selectively form terminal and bridging imido products. Furthermore, in coordinating solvent the complex abstracts the terminal N‐atom of mesityl azide to form a bridging nitrido.